DEVELOPING A DAYAK LEGEND STORYBOOK BASED ON TEXT DRIVEN APPROACH FOR TEACHING NARRATIVE TEXT (A Design and Development Research to Year-9 Students of SMP Negeri 1 Bengkayang in Academic Year 2022/2023) - Susanti, Yuni; Sutapa Yuliana, Yohanes Gatot; Ikhsanudin, Ikhsanudin (TELL - US JOURNAL, 2023)
The purpose of this research was to develop a Dayak Legend Storybook as supplementary materials for Ninth-year students. The basic thought underlying this study was to provide teachers and students with a Dayak legend story based on their background. The storybook was developed in five stages: analysis; design; development; implementation; and evaluation (ADDIE). The data was obtained through questionnaires, interviews, checklists, and field notes. Based on the findings, the storybook is worth utilizing due to its usefulness and the positive responses were given by the students, teacher, and validators to the contents. In conclusion, this study was successful in developing a qualified Dayak Legend Storybook as supplementary materials for Ninth year students.